ECMO for Neonatal Sepsis in 2019 - Butt, Warwick Wolf; Chiletti, Roberto (Frontiers in Pediatrics, 2020)
Sepsis and Septic shock in newborns causes mortality and morbidity depending on the organism and primary site. ECMO provides cardiorespiratory support to allow adequate organ perfusion during the time for antibiotics and source control surgery (if needed) to occur. ECMO mode and cannulation site vary depending on support required and local preference. Earlier and more aggressive use of ECMO can improve survival.